HISTORIOFIGURE Y OF INDIGENOUS EDUCATION PUBLIC POLICIES: A CUT FROM THE 1988 FEDERAL CONSTITUTION TO CONTEMPORANEITY - Marchetti, Cristiane Teixeira Bazilio; de Moraes, Nelson Russo; de Carvalho, Alonso Bezerra (Seven Editora, 2025)
The present article is an excerpt from a chapter, the result of the author's master's thesis in which she analyzed the historical and legal trajectory of public education policies aimed at indigenous peoples in Brazil. It was based on a qualitative and descriptive approach, grounded in historioFigure ical research and document analysis. The study highlights the transformations that have occurred since the Federal Constitution of 1988, a legal milestone that consolidated the right to differentiated education until the mid-2017 with the promulgation of the BNCC, in order to characterize such policies in their respective potentialities and/or weaknesses. The discussions highlight the indigenous protagonism in the conquest of their rights and the slow construction of public policies that recognize the cultural and linguistic diversity of these peoples. The analysis presented here demonstrates that, although legal advances have occurred, structural challenges still persist in the implementation of intercultural, bilingual, and contextualized indigenous school education.DOI: https://doi.org/10.56238/sevened2025.038-081